Evaluating the Psychometric Properties of Neurodevelopmental Assessment Tools in a South African Context - Zieff, Michal R (Department of Paediatrics and Child Health, 2022)
Neurodevelopmental and behavioural tools, used to assess children's cognitive and psychological development, play important supportive roles in clinical decision-making processes. It is therefore important that inferences made based on the information generated by these tools are valid and reliable. Because validity and reliability are inextricably tied to the context in which the tool is administered, it is critical that tools, including established “gold standard” tools, undergo ongoing psychometric evaluation. This is particularly important when tools are used in contexts different to that in which the original tool was developed. The use of poorly performing measures in clinical settings may result in a higher risk of misinterpretation of results or misdiagnosis, carrying serious implications for provision of interventions. This dissertation explored the psychometric properties of two frequently used behavioural tools in a South African context. The first aim of the dissertation was to investigate the use, cultural appropriateness, and psychometric soundness of Achenbach System of Empirically Based Assessment (ASEBA) forms in sub-Saharan Africa. The ASEBA forms are used worldwide to screen children and adolescents for behavioural and emotional problems. To achieve this aim, I conducted a systematic review of the psychometric properties of the ASEBA forms in sub-Saharan Africa. The second aim was to evaluate the structural and construct validity of a commonly used measure of AttentionDeficit/Hyperactivity Disorder (ADHD), the Swanson, Nolan, and Pelham ADHD Rating Scale (SNAP-IV), in a sample of South African children with neurodevelopmental disorders (NDDs), including Autism Spectrum Disorder and Intellectual Disability. The systematic review identified 58 studies with sub-Saharan African participants that reported measurement properties of the ASEBA forms. Most studies came from Southern (n = 29, 50%) or East African (n = 25, 43%) countries. Forty-nine studies (84%) used translated versions of the tool, but details regarding the translation process, if available, were often sparse. Most studies (n = 47, 81%) only reported internal consistency (using coefficient alpha) for one or more subscales. The methodological quality of the psychometric evaluations varied considerably across all measurement properties, except for internal consistency. There is limited good quality psychometric evidence available for the ASEBA forms in sub-Saharan Africa. Recommendations include implementing a standardised procedure for conducting and reporting translation processes and conducting more comprehensive psychometric evaluations of the translated versions of the tools. Parents of 109 children with one or more diagnosed NDDs completed the SNAP-IV. A subset of parents (n = 79) also completed the ASEBA Child Behaviour Checklist (CBCL/6-18). We conducted a confirmatory factor analysis to inspect the two-factor structure of the SNAP-IV (Inattention + Hyperactivity-Impulsivity). We also calculated ordinal coefficient alpha (α) to estimate internal consistency. Finally, we correlated scores of SNAP-IV and CBCL/6-18 subscales to estimate concurrent, convergent (ADHD + externalizing behaviour), and discriminant (ADHD + internalizing behaviour) validity respectively. The two-factor model performed acceptably (χ2 (134) = 249.82, p < 0.001, TLI = 0.868, RMSEA = 0.089, p < 0.001). The model fit improved after removing three problematic items, two of which were dependent on the child's level of spoken language (χ2 (89) = 135.17, p < 0.01, TLI = 0.942, RMSEA = 0.069, p = 0.096). The revised SNAP-IV subscales had acceptable internal consistencies (α = 0.85-0.86). Correlation coefficients between the SNAP-IV and ADHD-related CBCL/6-18 subscales were significant (r = 0.53- 0.62, p < 0.001). Correlations between ADHD and externalizing behaviours (r = 0.45, p < 0.001) and internalizing behaviours (r = 0.38, p < 0.001) respectively were not significantly different (z = 0.97, p = 0.165). The findings tentatively support the use of the SNAP-IV in this group of children. However, there are limitations to its performance in this population likely related to the presence of NDDs. Taken together, the findings of these two studies highlight the need for clinicians and researchers to conduct ongoing psychometric testing of behavioural tools for use with linguistically and culturally diverse sub-Saharan African populations. The data also reveal important insights regarding problems associated with using standard behavioural tools in children with complex clinical presentations.